Compound Specific Trends of Chemical Defences in Ficus Along an Elevational Gradient Reflect a Complex Selective Landscape - Volf, Martin; Laitila, Juuso E; Kim, Jorma; Sam, Legi; Sam, Katerina; Isua, Brus; Sisol, Mentap; Wardhaugh, Carl W; Vejmelka, Frantisek; Miller, Scott E; Weiblen, George D; Salminen, Juha-Pekka; et al. (Journal of chemical ecology, 2020)
Elevational gradients affect the production of plant secondary metabolites through changes in both biotic and abiotic conditions. Previous studies have suggested both elevational increases and decreases in host-plant chemical defences. We analysed the correlation of alkaloids and polyphenols with elevation in a community of nine Ficus species along a continuously forested elevational gradient in Papua New Guinea. We sampled 204 insect species feeding on the leaves of these hosts and correlated their community structure to the focal compounds. Additionally, we explored species richness of folivorous mammals along the gradient. When we accounted for Ficus species identity, we found a general elevational increase in flavonoids and alkaloids. Elevational trends in non-flavonol polyphenols were less pronounced or showed non-linear correlations with elevation. Polyphenols responded more strongly to changes in temperature and humidity than alkaloids. The abundance of insect herbivores decreased with elevation, while the species richness of folivorous mammals showed an elevational increase. Insect community structure was affected mainly by alkaloid concentration and diversity. Although our results show an elevational increase in several groups of metabolites, the drivers behind these trends likely differ. Flavonoids may provide figs with protection against abiotic stressors. In contrast, alkaloids affect insect herbivores and may provide protection against mammalian herbivores and pathogens. Concurrent analysis of multiple compound groups alongside ecological data is an important approach for understanding the selective landscape that shapes plant defences.
Keywords: flavonoidy; savci; Plant Leaves; společenstvo; Flavonoids; Alkaloids; alkaloidy; hmyz; feromony; Food Chain; Possum; Ficus; New Guinea; zvířata; Biota; Mammals; listy rostlin; býložravci; Coleoptera; Phenanthroindolizidine alkaloids; Insecta; Herbivory; Pheromones; Polyphenols; Altitude; Lepidoptera; Papua New Guinea; Animals; Folivorous mammals; Tannins; Papua Nová Guinea; potravní řetězec; nadmořská výška